2019
DOI: 10.1039/c9ra05111b
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated component-incorporated quaternized poly(phthalazinone ether ketone) membranes with improved ion selectivity, stability and water transport resistance in a vanadium redox flow battery

Abstract: Novel AIEMs were prepared through successive blending and amination processes, and they exhibited good ion selectivity, stability and water transport resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Chen et al [132][133][134] exploited new AIEMs based on poly (phthalazinone ether ketone) without electrostatic interactions of cationic and anionic groups. A small amount of sulfonated poly (phthalazinone ether ketone) (SPPEK) with different values of ion exchange capacity (IEC) was mixed with brominated poly (phthalazinone ether ketone) (BPPEK), after which the mixture is aminated in trimethylamine to obtain amphoteric membranes named Q/S-x where x represents the IEC value of SPPEK.…”
Section: Membranes Recently Developed For Vrfbmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [132][133][134] exploited new AIEMs based on poly (phthalazinone ether ketone) without electrostatic interactions of cationic and anionic groups. A small amount of sulfonated poly (phthalazinone ether ketone) (SPPEK) with different values of ion exchange capacity (IEC) was mixed with brominated poly (phthalazinone ether ketone) (BPPEK), after which the mixture is aminated in trimethylamine to obtain amphoteric membranes named Q/S-x where x represents the IEC value of SPPEK.…”
Section: Membranes Recently Developed For Vrfbmentioning
confidence: 99%
“…A small amount of sulfonated poly (phthalazinone ether ketone) (SPPEK) with different values of ion exchange capacity (IEC) was mixed with brominated poly (phthalazinone ether ketone) (BPPEK), after which the mixture is aminated in trimethylamine to obtain amphoteric membranes named Q/S-x where x represents the IEC value of SPPEK. 132 The Q/S-1.37 membrane has good ionic selectivity, chemical stability and high resistance to water transfer. Sulfonated poly (phthalazinone ether ketone) (SPPEK) and brominated poly (aryl ether ketone) containing 3,5-dimethylphthalazinone groups (BPPEK) were also mixed and then quaternized to form a series of amphoteric exchange membranes (Q/S-AIEM).…”
Section: Membranes Recently Developed For Vrfbmentioning
confidence: 99%
“…34 According to the Grotthuss mechanism, sulfonic groups aid the transportation of ions in water. 1,35 The sulfonation of 2,3-dialdehyde cellulose with bisulfite is an attractive synthesis route, as it can be conducted in an efficient manner under mild aqueous reaction conditions and without the use of harmful solvents. 14,19,36,37 The results revealed that NaIO 4 treatment for 24 h resulted in increased BC sulfonation than treatment for 48 h (Figure 7).…”
Section: Effects Of Modification Of Bc As a Templatementioning
confidence: 99%
“…Amphoteric membranes, which have both cations and anions covalently bonded to their structures, have been synthesized and characterized to maintain good conductivity while lowering vanadium permeability. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] Studies have characterized the permeability of vanadium ions across the membrane, but such studies often do not consider the migrative flux of vanadium that may dominate in working VRFBs. Equation 6shows a non-dimensional parameter, M D, that may be helpful to quantify the significance of migration in VRFBs.…”
Section: Symbolmentioning
confidence: 99%